2022
DOI: 10.1093/nar/gkac573
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of SAMHD1 Thr592 increases C-terminal domain dynamics, tetramer dissociation and ssDNA binding kinetics

Abstract: SAM and HD domain containing deoxynucleoside triphosphate triphosphohydrolase 1 (SAMHD1) is driven into its activated tetramer form by binding of GTP activator and dNTP activators/substrates. In addition, the inactive monomeric and dimeric forms of the enzyme bind to single-stranded (ss) nucleic acids. During DNA replication SAMHD1 can be phosphorylated by CDK1 and CDK2 at its C-terminal threonine 592 (pSAMHD1), localizing the enzyme to stalled replication forks (RFs) to promote their restart. Although phospho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 46 publications
4
18
0
Order By: Relevance
“…3b-c ) led to a concentration-dependent transition away from the Tm 1 at 40-45°C to Tm 2 at 57-60°C, with the latter being the only observed species at 5 mM GTP. Despite variations in the content of folded apo-protein across individual experiments, the observed Tm’s are in good agreement with the known equilibrium between mono- and dimeric species for recombinant SAMHD1 61 , and with recently published thermal shift data for SAMHD1 by Orris et al 62 . While the latter study only quotes the first transition between 44-46°C, the figures clearly show two transitions for SAMHD1 in the absence of ligands, which we interpret as representing monomeric (Tm 1 ) and dimeric (Tm 2 ) species, respectively.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…3b-c ) led to a concentration-dependent transition away from the Tm 1 at 40-45°C to Tm 2 at 57-60°C, with the latter being the only observed species at 5 mM GTP. Despite variations in the content of folded apo-protein across individual experiments, the observed Tm’s are in good agreement with the known equilibrium between mono- and dimeric species for recombinant SAMHD1 61 , and with recently published thermal shift data for SAMHD1 by Orris et al 62 . While the latter study only quotes the first transition between 44-46°C, the figures clearly show two transitions for SAMHD1 in the absence of ligands, which we interpret as representing monomeric (Tm 1 ) and dimeric (Tm 2 ) species, respectively.…”
Section: Resultssupporting
confidence: 89%
“…3d-e, dGTPαS concentration-dependently stabilised SAMHD1 beyond the first two transitions and elevated its melting temperature to a third Tm3 close to 70°C, which likely represents the tetrameric species. The observation of such significant stabilisation is also in agreement with the study by Orris et al 62 , although they used elevated dGTPαS concentrations at 2 mM and observed a higher Tm3 of 74-76°C across different SAMHD1 forms. Our data clearly shows how dGTPαS is a more potent stabiliser of SAMHD1, as the first (monomer) transition is largely lost already at 0.25 mM concentration.…”
Section: Th6342 and Analogues Deterred Recombinant Samhd1 Oligomerisa...supporting
confidence: 92%
“…Previously, we suggested that high dNTP levels found in cycling cells promote tetramerisation and catalytic activity of an unstable phospho-T592 SAMHD1 [ 5 ] and proposed this as an explanation for why phosphorylated SAMHD1 was still active in vitro. Although there are many conflicting reports, similar observations were reported by Bhattacharya et al [ 34 ], and more recently by Orris et al [ 57 ], where they found that phosphomimetic mutations affect the kinetics of tetramer assembly and disassembly, without affecting tetramerization equilibrium and overall triphosphohydrolase activity. Here, using our panel of T592 stable and unstable tetramer mutants (Fig.…”
Section: Discussionsupporting
confidence: 70%
“…Inhibition of ssDNA and ssRNA binding also likely arises from 5a blocking the A1 site that is used to bind to guanine nucleotides within nucleic acid sequences. 23,37 ■ CONCLUSIONS Although several unsuccessful library screens have been reported with SAMHD1, 31,46,47 and a nucleotide-based inhibitor with a methylene bridge connecting the α-phosphate and 5′-carbon has been described, 35 a general strategy with the potential for discovery of biologically active inhibitors is needed. In this regard, we have described an efficient strategy that has led to the first bifunctional small molecule ligand for SAMHD1 that inhibits both its dNTPase and nucleic acid binding activities.…”
Section: ■ Results and Discussionmentioning
confidence: 99%